Optimization and Computational Fluid Dynamics - Thévenin, Dominique; Janiga, Gábor (Springer Berlin Heidelberg : Imprint: Springer, 2008)
The numerical optimization of practical applications is an issue of growing importance in research and industry. It allows both the exploration of non-trivial configurations differing widely from all known solutions and the step-by-step improvement of existing designs. The purpose of this book is to introduce the state of the art concerning this issue, referred to in the book as CFD-based Optimization (CFD-O). Many complementary applications are presented, so that interested researchers and engineers will get a clear view of the present possibilities for all problems where the numerical optimization process relies on evaluations obtained through Computational Fluid Dynamics.